Inhibition of hypoxia inducible factor-1α ameliorates lung injury induced by trauma and hemorrhagic shock in rats - Jiang, Hong (Nature Publishing Group, 2012)
AIM: Ischemia/reperfusion is an initial triggering event that leads to gut-induced acute lung injury (ALI). In this study, we investigated whether hypoxia inducible factor-1α (HIF-1α) played a role in the pathogenesis of lung injury induced by trauma and hemorrhagic shock (T/HS). METHODS: Male Wistar rats underwent laparotomy and hemorrhagic shock for 60 min. Sham-shock animals underwent laparotomy but without hemorrhagic shock. After resuscitation for 3 hr, the rats were sacrificed. Morphologic changes of the lungs and intestines were examined. Bronchoalveolar lavage fluid (BALF) was collected. Lung water content, pulmonary myeloperoxidase (MPO) activity and the levels of malondialdehyde (MDA), nitrite/nitrate, TNF-α, IL-1β, and IL-6 in the lungs were measured. The gene expression of pulmonary HIF-1α and iNOS, and HIF-1α transcriptional activity in the lungs were also assessed. The apoptosis in the lungs was determined using TUNEL assay and cleaved caspase-3 expression. RESULTS: Lung and intestinal injuries induced by T/HS were characterized by histological damages and a significant increase in lung water content. Compared to the sham-shock group, the BALF cell counts, the pulmonary MPO activity and the MDA, nitrite/nitrate, TNF-α, IL-1β, and IL-6 levels in the T/HS group were significantly increased. Acute lung injury was associated with a higher degree of pulmonary HIF-1α and iNOS expression as well as apoptosis in the lungs. Intratracheal delivery of HIF-1α inhibitor YC-1 (1 mg/kg) significantly attenuated lung injury, and reduced pulmonary HIF-1α and iNOS expression and HIF-1α transcriptional activity in the T/HS group. CONCLUSION: Local inhibition of HIF-1α by YC-1 alleviates the lung injury induced by T/HS. Our results provide novel insight into the pathogenesis of T/HS-induced ALI and a potential therapeutic application.